Research in personnel and human resources management. - Buckley, M. Ronald; Wheeler, Anthony R.; Halbesleben, Jonathon R. B. (Research in personnel and human resources management ;, 2018)
Volume 36 of Research in Personnel and Human Resources Management contains seven chapters written by scholarly leaders in the field. Each chapter addresses an important area of current research in human resources management. This volume focuses on team leadership issues, job search processes, human resource technology systems, organizational citizenship behaviors, pregnancy issues at work, strategic human resources management, and emotions at work.